Identifikasi Masalah dan Solusi UMKM Sebagai Langkah Adaptasi dari Pandemi menggunakan Metode Kualitatif dan Kuantitatif (Studi Kasus: UMKM Ngijo Malang) - M. Rizky Kurniadi Ramadhan; Satrio Agung Wicaksono; Mochamad Chandra Saputra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
Micro, Small and Medium Enterprises (MSMEs) are a form of a productive economy run by middle to lower-class people. There are various benefits derived from the MSME sector, including improving the economy, reducing poverty, providing employment, and leading to the construction of social facilities. It is hoped that MSMEs can be more inclined to be innovative when facing threats and opportunities due to changing situations such as the result of the Covid-19 pandemic. In Indonesia, adaptation steps in dealing with the Covid-19 pandemic include the program of providing direct cash assistance to affected MSMEs. The problem that arises in the adaptation carried out by the government is that the MSME data registered with each local village government is not by the actual conditions. This raises other problems for MSMEs that are the target of the program, including the provision of assistance that is not on target. In this case, MSMEs need to adapt so that the problems experienced can be resolved. One that needs this adaptation plan is the MSMEs of Ngijo Village, Malang Regency. Ngijo's MSME problems can be explored by conducting in-depth interviews with MSME managers. After that, the results of the interviews can be analyzed using qualitative and quantitative methods. The identified problem will also be used as a dimension to measure the quality of the solution built and whether it can solve the problem or not. Researchers can draw conclusions that will be used to answer the formulation of the problem in this study such as the data collection process which is still manual using books making it difficult for the UMKM of Ngijo Malang Village to collect data. The transaction process is still carried out individually so it does not guarantee the security of the transaction process. The solution offered to overcome the problems faced by UMKM Ngijo Malang is a digital solution in the form of a website. This website was chosen because it can be accessed easily via an internet browser and is cross-platform compatible. Received an overall rating of 86.28% in the WebQual 4.0 assessment, which shows that website users as an MSME solution are quite effective in helping overcome Ngijo Malang's MSME problems.